1996
DOI: 10.1095/biolreprod54.1.173
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated polysaccharides inhibit lymphocyte-to-epithelial transmission of human immunodeficiency virus-1

Abstract: We have previously suggested that sulfated polysaccharides could be used in a vaginal formulation to inhibit infection by human immunodeficiency virus (HIV-1). This supposition was based on studies in which we developed and employed an in vitro model to simulate the mechanism of HIV-1 transmission during coitus. We found that adhesion of mononuclear cells to epithelia was the initial step in infection and speculated that blocking adhesion would prevent HIV-1 transmission. We observed that certain sulfated poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 35 publications
1
70
0
Order By: Relevance
“…Thorough characterization of vaginal and cervical epithelial cells, as well as HIV-1-infected mononuclear cells, has identified several relevant adhesion molecules, including ICAM-1 (46,47), that may facilitate the binding of infected cells to the epithelium (47,48). ICAM-1 is highly expressed by monocytes (49) and epithelial cells (46) and, to a lesser extent, by activated lymphocytes including HIV-1 infected CD4 ϩ T cells (47), and it plays a significant role in transendothelial migration of T lymphocytes and monocytes (20 -23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thorough characterization of vaginal and cervical epithelial cells, as well as HIV-1-infected mononuclear cells, has identified several relevant adhesion molecules, including ICAM-1 (46,47), that may facilitate the binding of infected cells to the epithelium (47,48). ICAM-1 is highly expressed by monocytes (49) and epithelial cells (46) and, to a lesser extent, by activated lymphocytes including HIV-1 infected CD4 ϩ T cells (47), and it plays a significant role in transendothelial migration of T lymphocytes and monocytes (20 -23).…”
Section: Discussionmentioning
confidence: 99%
“…ICAM-1 is highly expressed by monocytes (49) and epithelial cells (46) and, to a lesser extent, by activated lymphocytes including HIV-1 infected CD4 ϩ T cells (47), and it plays a significant role in transendothelial migration of T lymphocytes and monocytes (20 -23). In examining the mechanism by which anti-ICAM-1 Abs may block transepithelial transmission of HIV-1, our results show that in the in vivo HuPBL-SCID mouse model, the binding of the Ab to ICAM-1 on the murine reproductive epithelium is critical for blocking cell-associated transmission.…”
Section: Discussionmentioning
confidence: 99%
“…However, many women also need protection against unintended pregnancy, and therefore there is demand for the development of dual protection microbicides One non-contraceptive vaginal microbicide under intensive investigation at the Population Council for the prevention of HIV and sexually transmitted infections (STIs) in women is Carraguard (carrageenan PDR98-15: CARRA). Carrageenans have shown antiviral and antibacterial properties against HIV, herpes simplex virus-type 2 (HSV-2) and Neisseria gonorrhoeae [1][2][3][4][5][6]. The safety of vaginal administration has also been confirmed by laboratory and Phase 1 and 2 clinical studies [5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The product was tested for safety and efficacy in vitro in a cell-based model using HIV-1 IIIB (CXCR4 virus) (82) and an explant tissue-based model using HIV-1 BaL (CCR5 virus) (83). Human phase 1 studies for this product have shown that the product is safe to healthy women at low risk for HIV who were sexually abstinent (58), safe and acceptable in HIV-positive women who were sexually abstinent (84), and acceptable by both partners (85).…”
Section: Semisolids-hydrogelsmentioning
confidence: 99%